2022
DOI: 10.1029/2022jb024745
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic SV‐Wave Signatures of Fluid‐Saturated Porous Rocks Containing Intersecting Fractures

Abstract: Detecting fracture intersections is crucial for understanding rock hydraulic properties. For this purpose, we study the dynamic SV‐wave signatures of fluid‐saturated porous rocks containing intersecting fractures. A theoretical model is derived using the dynamic Biot's poroelasticity equations. Using this model, we analyze the features of SV‐waves and compare to those of previously studied P‐waves. The results show that the dispersion and attenuation of SV‐waves caused by elastic scattering and FF‐WIFF (Fractu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The anisotropy was distinctly different and complementary between SV-wave and fast P-wave. Especially, in the extreme case of unconnected fractures, the theoretical model of Guo, Gurevich et al (2022) indicated that SVwave had a much smaller dispersion and attenuation than fast P-wave.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The anisotropy was distinctly different and complementary between SV-wave and fast P-wave. Especially, in the extreme case of unconnected fractures, the theoretical model of Guo, Gurevich et al (2022) indicated that SVwave had a much smaller dispersion and attenuation than fast P-wave.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, fast P‐wave presented anisotropy, as the factures were not randomly aligned and their network was not isotropic in the macroscopic sense. For SV‐wave, the intersections of fractures also played a crucial role on the acoustic responses of such a rock (Guo, Gurevich, et al., 2022). The anisotropy was distinctly different and complementary between SV‐wave and fast P‐wave.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Guo, Zhao, et al (2022) derived a theoretical model using the Biot's dynamic poroelasticity equations to analyze the dispersion and attenuation of P-waves caused by FF-WIFF (Fracture-Fracture Wave-induced Fluid Flow). Then, they (Guo, Gurevich, & Chen, 2022) further analyzed the SV-waves using the same approach. Their work can be helpful for us to further extend the multiscale fracture model.…”
Section: Assessment Of the Modeling Approachmentioning
confidence: 99%